Pengaruh Jenis Mulsa terhadap Pertumbuhan dan Hasil Tiga Kultivar Kentang (Solanum tuberosum L.) yang Ditanam di Dataran Medium - Jajang Sauman Hamdani (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2009)
The objectives of the experiment were to study growth and yield of three potato (Solanum tuberosum L.) cultivars planted at medium altitude with different types of mulch. The experiment is located at experimental station of Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang at an altitude of about 680 m. The experiment was arranged in a Randomized Completed Block Design with factorial pattern, consisting of two factors and three replications. First factor was potato cultivar (Granola, Kennebec, and Panda), and the second factor was types of mulch, consisted of three levels : without mulch, straw mulch, and silver black polyethylene mulch. The result of the experiment showed that Panda cultivar had highest dry weight (29.5 g/plant) and leaf area (2513.7 cm2), while Granola cultivar had highest number of tuber per plant (15.17 knol/plant ) and highest tuber weight per plant was 650.6 g/plant (30.3 t.ha-1). Straw and silver black polyethylene mulches increased leaf area, dry weight, number of tuber per plant and tuber weight per plant. The effect of interaction betwen potato cultivar and source of mulch was significant on plant height. Panda cultivar and silver black polyethylene mulch resulted the highest height of plant (68.2 cm). Key words: Potato cultivar, mulch, medium altitude